Laparoscopic Splenectomy for Splenic Metastasis from Primary Lung Carcinoma - Carlos A. Lopera; Jean Pierre Vergnaud; Gustavo Matute-Turizo; Salin Pereira-Warr (Case Reports in Surgery)
Introduction. Isolated splenic metastases are a rare finding. Though several primary tumors can produce splenic metastases, including lung carcinoma, there are very few documented cases of isolated splenic metastases from lung carcinoma. This report presents such a case in which the splenic metastasis was removed with laparoscopic splenectomy. Presentation of Case. A 69-year-old woman with a history of lung carcinoma presented with several months of abdominal pain. Abdominal CT identified a splenic mass which was resected laparoscopically. Pathology confirmed a splenic metastasis from a primary large cell lung carcinoma. Discussion. Due to its anatomical and physiological characteristics, the spleen is a well-protected organ with respect to metastatic spread. The rarity of such metastases means that there is no evidence-based form of management. This case presents this rare metastatic occurrence and the successful management of the disease via laparoscopic splenectomy. Conclusions. This case confirms that splenic metastases can result from a primary lung carcinoma. Furthermore, the case supports successful management of this pathology by laparoscopic splenectomy.